High-throughput virus screening in crosses of South American and African cassava germplasm reveals broad-spectrum resistance against viruses causing Cassava Brown Streak Disease and Cassava Mosaic Virus Disease - Sheat, Samar; Zhang, Xiaofei; Winter, Stephan (MDPI, 2022)
Screening cassava lines for resistance against viruses causing cassava brown streak disease (CBSD) is cumbersome because of the unpredictable and erratic virus infections in the slow plant infection processes that are frequently not associated with distinct leaf symptoms and because of the reliance on the assessment of root necrosis as an indicator of plant resistance/tolerance. The selection of resistant candidates thus extends over several growing cycles and is still associated with uncertainties about the stage of virus infection. To reduce the time for selection of resistant crosses and the uncertainties associated with field screening, we have developed a fast-forward virus screening workflow to assess cassava seedlings from crosses of cassava brown streak- and cassava mosaic virus-resistant parents. After passing through an intensive and precise virus infection routine, cassava seedlings that carried resistance against cassava brown streak and mosaic viruses were identified. Taking the results of 195 seedlings from 18 crossing families together, it became evident that resistance against the viruses causing CBSD is a dominant trait. The protocol developed for virus resistance screening in cassava can be readily adopted. It shifts resistance evaluation from the field to the nursery and replaces the erroneous and lengthy virus infection and screening process with a method of precision and speed